Enhancement of iterative back projection technique for super resolution image / Amir Nazren bin Abdul Rahim. - Amir Nazren Abdul Rahim (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2018)
Based on the aforementioned problems, several objectives of this study are highlighted and divided into three main folds as follows ; The first objective is to improve the IBP reconstruction algorithm by increasing the de-blurring quality image output ; The second objective is to reduce the number iterations of the IBP reconstruction function ; The third objective is to enhance the level of robustness of the IBP method toward the ringing and additional noise effect.